Chlamydia trachomatis, Neisseria gonorrhoeae and human papillomavirus infections of lower genital tract of Indigenous women from Xingu Indigenous Park - Claudia Correa Porto; Adhemar Longatto-Filho; Bruna De Almeida; Tatiana Bonetti; Sula Fernanda Kamaiurá Ricardo Diaz; Thais Heinke; Fernanda Cury; Iara Santana; Mariana Queiroz; Douglas Rodrigues; Neila De Gois Speck (James Cook University, 2023)
Introduction: Xingu Indigenous Park (XIP) currently protects 16 ethnic Indigenous groups and is located in the central area of Brazil. XIP is the first and the largest Indigenous land to be recognized in the country. Community access is limited and restricted for the non-Indigenous population, and the Indigenous women are constantly dealing with shortages of medical care. High-risk human papillomavirus (HR-HPV) is the most common cause of cervical cancer and is detected in 99% of cervical precancers. HPV infections may be associated with bacterial agents such as Chlamydia trachomatis and Neisseria gonorrhoeae, which are also important causative agents of sexually transmitted infections and are responsible for the most frequent bacterial infections in the world. The present study evaluated the frequency and potential impact of Chlamydia trachomatis, Neisseria gonorrhoeae, and HR-HPV in the Indigenous women of XIP. Methods: In this cross-sectional study, 992 cervical-vaginal samples were collected from Indigenous women, using a Cervex-Brush, and were immediately placed in a SurePath medium. All samples were submitted to the cobas® 4800 detection system for the identification of 14 different types of HR-HPV, and the multiplex Abbott RealTime CT/NG assay for the detection of Chlamydia trachomatis and Neisseria gonorrhoeae. Results: HR-HPV was detected in 18.2% of women; 6% were positive for HPV16, 5% for HPV18, and 81% for other types of HR-HPV. Co-infections of HPV16 and other types was observed in 5% of women, and 3% had co-infections of HPV18 and other types. Moreover, 1.8% of women were positive for Chlamydia trachomatis, while Neisseria gonorrhoeae was not detected. In women with HR-HPV, 33% had Chlamydia trachomatis infections, 28% were positive for HR-HPV other than HPV16 or HPV18, and 5% had co-infections of HPV16 and the other types of HPV. Younger women were found to be more susceptible to HPV infections. Conclusion: The findings indicate a high frequency of HR-HPV and a considerable frequency of Chlamydia trachomatis in the Indigenous women of XIP. The detection of Chlamydia trachomatis, Neisseria gonorrhoeae, and/or HR-HPV does not present evidence of a potential interrelationship for a combined pathogenic action in these women.